Planning and spatial solutions for the integrated development of the territory of the Caucasian Mineral Waters agglomeration based on the specific historical background - N. A. Fomenko; A. D. Konovalov (Современная наука и инновации)
The economic efficiency of a region's development is inextricably linked with the formation of agglomerations on its territory. This process is based on the socio-economic policy of the Russian Federation, which is consistent with market principles and takes into account the specifics of agglomerations. Agglomerations are managed at the regional level. In Russia, new relationships have developed between the center and the subjects, which have determined the special position and role of agglomeration regions. The process of agglomeration formation is experiencing a new stage of development, acquiring a new spatial form. This is due to the need to study not only the content of the agglomeration region, but also the methods of managing these territorial entities. This article analyzes and explores the possibilities of an integrated planning solution that takes into account the historical features of the Caucasian Mineral Waters agglomeration. Attention is paid to both the advantages and disadvantages in the development of spatial concepts. Particular attention is paid to the problems associated with the development of the street and road network and the insufficient level of organization of bypass routes around cities. This, in turn, leads to an increase in transit traffic through resort cities, which creates additional difficulties for the tourism business and requires the search for new solutions.